Minat Siswa Dalam Pembelajaran Seni Budaya (Musik) Di SMP Negeri 3 Duo Koto Pasaman - Febrianto Ahmad; Ardipal Ardipal (SENDRATASIK UNP, 2020)
This research was conducted at SMP Negeri 3 Duo Koto Pasaman. The research objective was to describe students' interest in learning cultural arts (music) in class VII-3 at the school. This type of research is qualitative research with a descriptive approach. The research object was 36 students of class VII-3, with the research instrument being the researcher himself as the main researcher with additional instruments such as observation notes, interview notes and literature study. Data collection techniques through observation, interviews and documentation.While data analysis is by systematically classifying the data to draw conclusions. The factors that influence students' interest in learning are divided into two, namely internal and external factors. Internal factors in the form of attention, talent, interest and motivation, how to learn. And external factors in the form of family, school, and others. From the results of the research that the researchers observed covering the factors that influence student interest in learning, the results showed that the lack of student interest in learning the art of music at SMP Negeri 3 Duo Koto Pasaman was caused by a lack of strategies and methods used by teachers in the learning process. Teachers are more likely to provide material in the form of theory using the lecture method, so that students feel bored and not enthusiastic in participating in learning the art of music. Meanwhile, learning the art of music requires balanced learning in the form of theory and practice, to increase student interest in learning the art of music.